Reforms In Adult And Non-Formal Education In Nigeria For Quality Assurance - Okemakinde, Sunday O; Olajide, Muili F (Journal of Continuing and Development Education, 2023)
Adult and non-formal education plays a major role in the transformation of any society from illiterate to literate society. This makes the programme one of the most important factors to be reckoned with in the educational system in Nigeria. Policies were formulated and programmes like Basic literacy education, Mass literacy campaigns and so on were put in place by government to enable people contribute their quota to the nation’s growth positively. However, high illiteracy rate still persists because most of these programmes were unsuccessful due to some challenges facing the programmes ranging from poor policy implementation to inadequate funding just to mention but a few. This paper has identified some reforms put in place by government in order to enable Nigerians have access to basic education in the country. Full implementation of the programmes would go a long way in making it possible for Nigeria to be in the league of the development economy with a mass level of literacy. These include: Out-of-school Boy’s Education; Girl-child Education; Each-One-Teach-One or Fund-the-Teaching-of-One and Literacy by Radio. Recommendations are provided to ease the challenges facing adult and non-formal education programmes for quality assurance in Nigeria.